Comprehensive pain management strategy for infants with moderate to severe osteogenesis imperfecta in the perinatal period. Issue 4 (4th December 2021) - Carroll, Ricki S.; Donenfeld, Perri; McGreal, Cristina; Franzone, Jeanne M.; Kruse, Richard W.; Preedy, Catherine; Costa, Joanna; Dirnberger, Daniel R.; Bober, Michael B.
Abstract: Osteogenesis imperfecta (OI) is a rare genetic heterogeneous disorder that causes increased bone fragility and recurrent fractures. For infants with OI and diffuse fractures, pain management, which is nuanced and specific for this population, is of the utmost importance to their neonatal care. Through experience at our center, we have developed a standard approach that has been successful in optimizing survival for these infants during this tenuous period. In this paper, we outline our multidisciplinary approach to pain management for infants with moderate to severe OI during the neonatal period, with emphasis on promotion of fracture healing and adequate pain control.